Safety Analysis of different industries using Fuzzy AHP - Rajmohan, P.; Srinivasan, P.S.S. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In recent days, we march towards a new occupational health and safety era in which work cultures are directed towards positive safety values. It is predicted that the safety analysis techniques now in place are quite difficult to address the potential risks which weakens the era. A novel approach of analyzing different crucial criteria in different industrial sectors is analyzed carefully in this paper. In this unique approach, fuzzy AHP(Analytic Hierarchy Process) technique is applied to determine the respective weights of three main criteria and seventeen sub-criteria as a way of enriching the decision making process while in a dilemma. A survey was initiated in different industrial sectors to obtain reliable data for the research. The results shows that the main criteria ‘human safety’ acquired a weight of 72.5% while the respective weights of main criteria machine safety and work environment safety falls to 8.9% and 18.4%. The weight of the main criteria, human safety indicates that the sub-criteria such as eye protection, manual lifting, material handling practices, fire fighting drills, training and safety officers are implemented to a greater extent in most of the surveyed industries.